2015
DOI: 10.1136/postgradmedj-2014-133211
|View full text |Cite
|
Sign up to set email alerts
|

Imaging assessment of traumatic brain injury

Abstract: Traumatic brain injury (TBI) constitutes injury that occurs to the brain as a result of trauma. It should be appreciated as a heterogeneous, dynamic pathophysiological process that starts from the moment of impact and continues over time with sequelae potentially seen many years after the initial event. Primary traumatic brain lesions that may occur at the moment of impact include contusions, haematomas, parenchymal fractures and diffuse axonal injury. The presence of extra-axial intracranial lesions such as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(66 citation statements)
references
References 60 publications
0
55
2
7
Order By: Relevance
“…Both approaches have further refined our understanding of the localized and neural underpinnings of healthy and disrupted sleep, as well as of circadian variations in brain functions [68][69][70]. The use of neuroimaging methods such as positron emission tomography and structural and functional magnetic resonance imaging during sleep and wakefulness in concussed, recovered, and never concussed individuals remain scarce, but has a high potential to provide unique and novel insights into the underpinnings of sleep and circadian disturbances in mTBI, and therefore may guide the development of innovative and targeted diagnostic and therapeutic strategies [70][71][72][73][74][75].…”
Section: Advanced Sleep Measurement Methodsmentioning
confidence: 99%
“…Both approaches have further refined our understanding of the localized and neural underpinnings of healthy and disrupted sleep, as well as of circadian variations in brain functions [68][69][70]. The use of neuroimaging methods such as positron emission tomography and structural and functional magnetic resonance imaging during sleep and wakefulness in concussed, recovered, and never concussed individuals remain scarce, but has a high potential to provide unique and novel insights into the underpinnings of sleep and circadian disturbances in mTBI, and therefore may guide the development of innovative and targeted diagnostic and therapeutic strategies [70][71][72][73][74][75].…”
Section: Advanced Sleep Measurement Methodsmentioning
confidence: 99%
“…Previous studies have shown that TBI is associated with changes in brain structure and function (for recent reviews, see (Currie et al, 2016;Hannawi and Stevens, 2016;Hayes et al, 2016;Rincon et al, 2016). The most prominent anatomical alterations are changes in prefrontal cortex morphology (Cristofori and Levin, 2015;Killgore et al, 2016), volume loss (Farbota et al, 2012;Hulkower et al, 2013;Ross, 2011) and reduced whitematter integrity (for a review, see (Hulkower et al, 2013)) and cerebellar atrophy (Drijkoningen et al, 2015;Sidaros et al, 2009).…”
Section: Introductionmentioning
confidence: 95%
“…The purpose of fMRI is already being evaluated in other specialties. [55,[144][145][146][147][148][149] Ultra-high field MR scanners, the use of other MRI methods such as ASL, diffusion tensor imaging, magnetic resonance spectroscopy or the combination with EEG/MEG or functional near infrared spectroscopy should optimise attainment of such goals.…”
Section: Future Perspectivesmentioning
confidence: 99%